Borderline Dysplastic Hips With Femoroacetabular Impingement Syndrome Show Increased Axial Distraction Distance on an Intraoperative Traction Examination - Joseph Featherall, M.D.; Reece M. Rosenthal, M.D.; Allan K. Metz, M.D.; Benjamin T. Johnson, B.S.; Ameen Khalil, M.S.; Alexander J. Mortensen, M.D.; Travis G. Maak, M.D.; Stephen K. Aoki, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation)
Purpose: To compare distraction profiles of borderline dysplastic hips with hips of normal acetabular morphology. Methods: This study was a retrospective analysis of prospectively collected data. Intraoperative distraction profile, radiographic, and patient demographic data were compiled in a database. All patients with borderline dysplastic hips, as determined by a lateral center-edge angle of 18° to 25°, comprised the borderline dysplastic cohort. A cohort of hips with normal femoral head coverage comprised the normal coverage group. Demographic variables between groups were compared to ensure similarity. Between-group comparisons of axial distraction distance at 25, 50, 75, and 100 pounds-force (lbf) were conducted using the Student t test. A multivariable regression was conducted to control for covariates. Results: We identified 136 hips with normal coverage and 36 hips with borderline dysplasia for comparison. Demographic variables were similar between groups. The dysplastic group showed greater axial distractibility at 75 lbf of traction force (6.47 ± 2.95 mm vs 5.07 ± 3.11 mm, P = .016) and 100 lbf of traction force (9.47 ± 2.00 mm vs 7.95 ± 2.50 mm, P = .001). Multivariable linear regression showed that an increased distraction distance was associated with female patients, smaller alpha angles, and less coverage measured by the lateral center-edge angle. Conclusions: In a population undergoing hip arthroscopy for femoroacetabular impingement syndrome, patients with borderline hip dysplasia showed greater intraoperative axial distraction distances than patients with nondysplastic hips. Level of Evidence: Level III, retrospective cohort study.